An Ecological Study and Disparities Analysis of Stunting and Its Predictors in Indonesia Based on SSGI 2024 - Niken Agus Tianingrum; Reny Mareta Sari (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Stunting still remains a public health problem in Indonesia. Based on Indonesian Nutritional Status Survey (SSGI) 2024, the prevalence of stunting has declined over the past decade but remains high and varies considerably across the 36 provinces. This study aimed to describe ecological patterns and regional disparities in stunting prevalence and its predictors in Indonesia. This ecological study used secondary data from the SSGI 2024, with provinces as the unit of analysis. The dependent variable was provincial stunting prevalence, while independent variables included maternal knowledge, complete basic immunization, standard growth monitoring, iron supplementation, and access to safe drinking water. Bivariate analysis was conducted using scatter plots, and Spearman correlation tests were applied to assess associations. The results revealed clear disparities in stunting prevalence between western and eastern Indonesia, particularly across Sumatra, Java, and Bali. Provinces with higher coverage of complete basic immunization and better access to safe drinking water tended to have lower stunting prevalence. Conversely, higher coverage of growth monitoring was associated with higher stunting prevalence. Three variables were significantly associated with stunting prevalence: complete basic immunization (p-value = 0.03), standard growth monitoring (p-value = 0.007), and access to safe drinking water (p-value = 0.0002). The findings suggest that strengthening basic immunization, growth monitoring, and access to safe drinking water, particularly through optimizing POSYANDU as an integrated maternal and child health service may help reduce stunting prevalence in Indonesia.